2022
DOI: 10.3390/jcm11185310
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Organ-Specific Metastases in Patients with Metastatic Upper Tract Urothelial Carcinoma

Abstract: Background: Existing data on metastatic upper tract urothelial carcinoma (mUTUC) are limited. In this study, we investigated the prognostic value of site-specific metastases in patients with mUTUC and its association with survival outcomes. Methods: We retrospectively collected data from the Surveillance, Epidemiology and End Results (SEER) database between 2004 and 2016. Kaplan–Meier analysis with a log-rank test was used for survival comparisons. Multivariate Cox regression was employed to predict overall su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…The proportion of RPI invasion at the primary site in UTUC is not clear. Some studies have reported that the percentage of renal pelvis cancers in UTUC were around 65%, and 25–50% of UTUC cases were above T3 27–29 . The number of T3 cases in our UTUC cohort was quite large (48 cases; 75.0%), and the number of cases with RPI was also large (23 cases; 35.9%).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The proportion of RPI invasion at the primary site in UTUC is not clear. Some studies have reported that the percentage of renal pelvis cancers in UTUC were around 65%, and 25–50% of UTUC cases were above T3 27–29 . The number of T3 cases in our UTUC cohort was quite large (48 cases; 75.0%), and the number of cases with RPI was also large (23 cases; 35.9%).…”
Section: Discussionmentioning
confidence: 64%
“…Some studies have reported that the percentage of renal pelvis cancers in UTUC were around 65%, and 25-50% of UTUC cases were above T3. [27][28][29] The number of T3 cases in our UTUC cohort was quite large (48 cases; 75.0%), and the number of cases with RPI was also large (23 cases; 35.9%). The high rate of RPI in our cohort was probably because many patients were referred to our hospital for differentiation from renal cancer.…”
Section: Discussionmentioning
confidence: 93%
“… 16 In a large retrospective study on metastatic upper UC, the most common site of metastasis was identified as the distant lymph nodes, and liver metastasis was found to be a poor prognostic factor, whereas primary tumour resection and chemotherapy were predictors of better survival outcome. 17 The development of cisplatin-based combination chemotherapy has extended median survival from several to 11–15 months. 16 However, the prognosis for metastatic patients with no response to primary chemotherapy is poor.…”
Section: Discussionmentioning
confidence: 99%
“…Bladder urothelial carcinoma is a highly heterogeneous disease with varying clinical outcomes. Patients with the same tumor stage may have different survival outcomes [ 2 , 3 , 4 , 5 , 42 ]. The survival rates correlate directly with the cancer cell proliferation, migration, and invasion of bladder cancer.…”
Section: Discussionmentioning
confidence: 99%